REDUCING SPEAKING ANXIETY BY ENCOURAGING STUDENTS’ ENGAGEMENT IN EFL CLASSROOMS THROUGH ARTIFICIAL INTELLIGENCE: A LITERATURE REVIEW - siska, Siska; Satria, Willy; Ikhsan, M.Khairi; yelliza, Yelliza (Universitas PGRI Sumatera Barat, 2025)
This review research explores some benefits that purposed by the integration of Artificial Intelligence in EFL classroom, mainly in improving students’ engagement and involvement in the learning process so that their anxiety while speaking could be dismissed . Some AI tools that could be used in teaching speaking like Intelligent Tutoring Systems, speech recognition technologies, Chatsbot, Kahoot and AI-based feedback mechanism which encourage students engagement and self-confidence in speaking practice. Research from various experts, such as (Turner & Patrick, 2004), Karim et al., 2023; Kholis, 2021; Samad & Ismail, 2020). Mardhiah, Ainol, et al (2024) show that the integration AI in English learning and teaching could improve the students’ activeness and engagement and allow them to practice more that create the enjoyable learning setting without feeling anxiety. However, there are some challenges and constraints in applying Artificial Intelligence such as the limitation of natural adaptation and communication in the real context, less direct corrective feedback, and less human interaction. To solve these problems, combining the strengths of AI with teacher traditional methods, offers a richer and more adaptable learning experience that better meets the diverse needs of students.